2022
DOI: 10.1002/adfm.202209853
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Intrinsic Superconductivity of the Nb/BiSbTe2Se Interface

Abstract: Typically, topological superconductivity is reachable via proximity effect by a direct deposition of superconductor (S) on top of a topological insulator (TI) surface. Here, the double critical current in the Josephson junctions based on the topological insulator is observed in the fabricated planar Superconducting Quantum Interference Devicea. By measuring critical currents as a function of temperature and magnetic field, it is shown that the second critical current stems from the intrinsic superconductivity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Therefore, the fact that the experimental dependence coincides with the theoretical dependence for purely ballistic contacts does not provide a clear indication as to which of the structures (SNS or SINIS) was actually studied. Thus, in [ 45 ], the presence of two critical currents was detected in the structures obtained by sputtering of Nb on top of Fe-doped BiSbTe 2 Se flake. According to the authors, the existence of the second critical current results from the intrinsic superconductivity of the Nb–Fe-doped BiSbTe 2 Se interface.…”
Section: Discusionmentioning
confidence: 99%
“…Therefore, the fact that the experimental dependence coincides with the theoretical dependence for purely ballistic contacts does not provide a clear indication as to which of the structures (SNS or SINIS) was actually studied. Thus, in [ 45 ], the presence of two critical currents was detected in the structures obtained by sputtering of Nb on top of Fe-doped BiSbTe 2 Se flake. According to the authors, the existence of the second critical current results from the intrinsic superconductivity of the Nb–Fe-doped BiSbTe 2 Se interface.…”
Section: Discusionmentioning
confidence: 99%
“…Recently, some papers have reported this effect at the heterojunction between the superconductor and TI. [ 4 ] These phenomena enable the development of quantum computers, spintronics, and novel optoelectronics. [ 5,6 ] However, only a few studies have reported the “superconducting proximity effect” on the heterojunction between HTS and TI.…”
Section: Introductionmentioning
confidence: 99%